2020
DOI: 10.3847/1538-4357/abb8db
|View full text |Cite
|
Sign up to set email alerts
|

Standing on the Shoulders of Giants: New Mass and Distance Estimates for Betelgeuse through Combined Evolutionary, Asteroseismic, and Hydrodynamic Simulations with MESA

Abstract: We conduct a rigorous examination of the nearby red supergiant Betelgeuse by drawing on the synthesis of new observational data and three different modeling techniques. Our observational results include the release of new, processed photometric measurements collected with the space-based Solar Mass Ejection Imager instrument prior to Betelgeuse's recent, unprecedented dimming event. We detect the first radial overtone in the photometric data and report a period of 185±13.5 days. Our theoretical predictions i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
54
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(65 citation statements)
references
References 112 publications
(196 reference statements)
10
54
0
1
Order By: Relevance
“…Interferometric observations of Betelgeuse by Haubois et al (2009), Chiavassa et al (2010), Ohnaka et al (2011), and Montargès et al (2016) have shown evidence for the presence of large convective cells in its atmosphere, which is in accordance with predictions by Schwarzschild (1975). The photometric periodicity of Betelgeuse is characterized by two main periods: a short one of about 400 days and a long one of about 2000 days (Kiss et al 2006;Joyce et al 2020). Mechanisms such as atmospheric pulsations in the fundamental or low-overtone modes and oscillations excited by convection cells were invoked to explain the short photometric period (Kiss et al 2006;Joyce et al 2020).…”
Section: Betelgeuse Is One Of the Closest (222 +48supporting
confidence: 56%
See 1 more Smart Citation
“…Interferometric observations of Betelgeuse by Haubois et al (2009), Chiavassa et al (2010), Ohnaka et al (2011), and Montargès et al (2016) have shown evidence for the presence of large convective cells in its atmosphere, which is in accordance with predictions by Schwarzschild (1975). The photometric periodicity of Betelgeuse is characterized by two main periods: a short one of about 400 days and a long one of about 2000 days (Kiss et al 2006;Joyce et al 2020). Mechanisms such as atmospheric pulsations in the fundamental or low-overtone modes and oscillations excited by convection cells were invoked to explain the short photometric period (Kiss et al 2006;Joyce et al 2020).…”
Section: Betelgeuse Is One Of the Closest (222 +48supporting
confidence: 56%
“…The photometric periodicity of Betelgeuse is characterized by two main periods: a short one of about 400 days and a long one of about 2000 days (Kiss et al 2006;Joyce et al 2020). Mechanisms such as atmospheric pulsations in the fundamental or low-overtone modes and oscillations excited by convection cells were invoked to explain the short photometric period (Kiss et al 2006;Joyce et al 2020). The long photometric variations were proposed to be due to binarity or magnetic activity (Wood et al 2004), or turnover of giant convection cells (Stothers 2010).…”
Section: Betelgeuse Is One Of the Closest (222 +48mentioning
confidence: 99%
“…Measurements 40 obtained in June-July 2020 showed that Betelgeuse experienced another dimming not corresponding to the 400 days period, but it has recovered since 41 . These successive dimmings fall within the irregular pattern of light curve variability of the star, and can be attributed to pulsation/convective activity 6 . Our results confirm that the Great Dimming is not an indication of Betelgeuse's imminent explosion as a supernova 6,24 (SN).…”
Section: /19mentioning
confidence: 81%
“…These successive dimmings fall within the irregular pattern of light curve variability of the star, and can be attributed to pulsation/convective activity 6 . Our results confirm that the Great Dimming is not an indication of Betelgeuse's imminent explosion as a supernova 6,24 (SN). Interpretation of the early behavior of core-collapse SNe light curves and post collapse spectral line variation point to enhanced pre-SN mass loss in the final weeks to centuries of the stars' life 42 , in at least part of the progenitor population.…”
Section: /19mentioning
confidence: 81%
“…Az akkori mérések szerint úgy gondolták, a Betelgeuze távolsága 181 fényév, ebből pedig kiszámítható, hogy a csillag átmérője 2,6 CSE (a csillagászati egység a Nap és a Föld közötti átlagos távolság, 150 millió km). Többek között magyar hozzájárulásnak (Molnár László) is köszönhetően ma már tudjuk, hogy a csillag háromszor messzebb van, mint Michelsonék hitték (Joyce et al, 2020). A látszó méretére kapott érték viszont ma is pontosnak számít, az új távolságértékkel tehát a csillag átmérője mintegy 7 CSE.…”
Section: Egy Bugyborékoló Szuperóriás Csillagunclassified